Factors influencing use of an e-health website in a community sample of older adults. - Czaja SJ; Sharit J; Lee CC; Nair SN; Hernández MA; Arana N; Fu SH; Czaja, Sara J; Sharit, Joseph; Lee, Chin Chin; Nair, Sankaran N; Hernández, Mario A; et al. (Journal of the American Medical Informatics Association, 2013)
Objective: The use of the internet as a source of health information and link to healthcare services has raised concerns about the ability of consumers, especially vulnerable populations such as older adults, to access these applications. This study examined the influence of training on the ability of adults (aged 45+ years) to use the Medicare.gov website to solve problems related to health management. The influence of computer experience and cognitive abilities on performance was also examined.Design: Seventy-one participants, aged 47-92, were randomized into a Multimedia training, Unimodal training, or Cold Start condition and completed three healthcare management problems. MEASUREMENT AND ANALYSES: Computer/internet experience was measured via questionnaire, and cognitive abilities were assessed using standard neuropsychological tests. Performance metrics included measures of navigation, accuracy and efficiency. Data were analyzed using analysis of variance, χ(2) and regression techniques.Results: The data indicate that there was no difference among the three conditions on measures of accuracy, efficiency, or navigation. However, results of the regression analyses showed that, overall, people who received training performed better on the tasks, as evidenced by greater accuracy and efficiency. Performance was also significantly influenced by prior computer experience and cognitive abilities. Participants with more computer experience and higher cognitive abilities performed better.Conclusions: The findings indicate that training, experience, and abilities are important when using complex health websites. However, training alone is not sufficient. The complexity of web content needs to be considered to ensure successful use of these websites by those with lower abilities.